Analisis Faktor-faktor Yang Mempengaruhi Minat Menggunakan Bank Digital Syariah pada Generasi Z: Studi Kasus di Kota Bogor - Cupian Cupian; Ugi Valentino; Sarah Annisa Noven (Jurnal Ilmiah Ekonomi Islam, 2022)
Islamic digital banks is an innovation in the Islamic banking industry. The three things of Islamic digital banks are interesting to study. First, increase the competitiveness with the emergence of Islamic digital banks. Second, the rapid development of technology trigger digital banks as an adaptation to the new era. Third, rapid adaptation makes digital banks a new trend in the banking industry that triggers new findings. This study aimed to determine the factors influencing the intention to use Islamic digital banks. Understanding the intention to use an Islamic digital bank is very useful in forming an ideal Islamic digital bank. It is expected to be a finding to increase the competitiveness and adaptation of Islamic banks. This study used 100 Generation Z samples located in Bogor city. The method used is a descriptive quantitative method with SEM-PLS analysis which is a multivariate analysis. Therefore, the results in this study have a significant effect on the perceived credibility and social influence variables. In contrast, the perceived ease of use and usefulness variables have no significant impact on the intention of use’s variables.